2013
DOI: 10.1186/1476-072x-12-1
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the application and utility of geographical information systems for exploring disease-disease relationships in paediatric global health research: the case of anaemia and malaria

Abstract: Malaria and anaemia are important health problems among children globally. Iron deficiency anaemia may offer protection against malaria infection and iron supplementation may increase the risk of malaria-related hospitalization and mortality. The nature and mechanism of these relationships, however, remain largely unresolved, resulting in concern and uncertainty around policies for non-selective iron supplementation in malaria endemic areas. Use of geographical information systems (GIS) to investigate this dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
100
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(102 citation statements)
references
References 25 publications
1
100
1
Order By: Relevance
“…Although not statistically significant, the point estimates are consistent with other studies that have largely shown positive associations between artificial light at night exposure and breast cancer risk 2125 and are in line with a meta-analysis reporting a 17% increase in overall breast cancer risk for artificial light exposure. 8 We were limited by not having additional information about artificial light in the evenings prior to bedtime or on duration of light exposure during sleep.…”
Section: Discussionsupporting
confidence: 89%
“…Although not statistically significant, the point estimates are consistent with other studies that have largely shown positive associations between artificial light at night exposure and breast cancer risk 2125 and are in line with a meta-analysis reporting a 17% increase in overall breast cancer risk for artificial light exposure. 8 We were limited by not having additional information about artificial light in the evenings prior to bedtime or on duration of light exposure during sleep.…”
Section: Discussionsupporting
confidence: 89%
“…It also improves our understanding of neighborhood effects on health by focusing on neighborhood concentrated disadvantage in addition to poverty – a broader indicator or neighborhood quality that is consistent with Wilson's insights on concentration effects (Wilson, 1987), the social disorganization literature (Sampson and Groves, 1989), a recent analysis of delinquency among MTO youth (Graif 2015a), and research on the neighborhood effects on other health outcomes in varying social groups and countries (Allender et al, 2012; Caughy et al, 2007; Sridharan et al, 2007; Zhang et al, 2011; Zhang et al, 2013). Our results show that exposure to residential neighborhood disadvantage is associated with worse mental health, as expected.…”
Section: Discussionmentioning
confidence: 71%
“…In contrast, deprived areas proximal to advantaged areas have been found to have higher rates of anxiety/mood disorder treatment (Pearson, 2013). Other studies have examined how spatial integration of deprived neighborhoods affects health outcomes other than mental health (Allender et al, 2012; Cuaghy et al, 2007; Chen et al, 2010; Lorant et al, 2001; Sridharan, 2007; Zhang et al, 2011; Zhang et al, 2013). …”
mentioning
confidence: 99%
“…Many systems incorporated a temporal component, enabling either animation of data through time or restriction of the data displayed to a time window of interest [77, 79, 84, 110]. A step beyond mere display of information, some GIS or spatial statistical methods seek to perform kernel-based smoothing to estimate risk maps [87, 97, 107], visualize disease risk according to a statistical model [29, 46, 76, 81, 85, 86, 107, 111, 112], or compare one feature to another [71, 84, 97, 100, 101]. While the ability to zoom and pan to navigate maps [79, 96, 105] is a common interactive feature enjoyed by users, more advanced systems contain interactive controls to enable users to retrieve information about selected items or regions, visualize the results of arbitrary queries [79], control visualization options, control temporal ranges of data returned [77, 79], or link displays of data with alternate or comparative visualizations [78, 79].…”
Section: Resultsmentioning
confidence: 99%